Prediction of long-term performance and definition of a moisture conversion factor for the durability design of pultruded GFRP profiles under hygrothermal exposure. (4th April 2022) - Garrido, M.; Sousa, J.M.; Correia, J.R.; Cabral-Fonseca, S.
Highlights: Arrhenius-based methodology to predict pultruded GFRP mechanical properties retention. Overall better performance of vinyl ester resin matrix over unsaturated polyester. Survey of degradation data from the literature shows high dispersion. Available data indicates that current design guidelines are often non-conservative. Moisture conversion factor proposed for the durability design of pultruded GFRP profiles. Abstract: This paper presents long-term prediction models for the mechanical property retention of pultruded GFRP materials, with either isophthalic unsaturated polyester or vinyl ester resin, derived from a set of experimental results gathered over a period of two years of accelerated ageing under hygrothermal exposure. The prediction models were fitted to experimental data of mechanical property retention for profiles immersed in water and salt water at 20 °C, 40 °C, and 60 °C, and under continuous condensation at 40 °C; the predictions were compared to other models available in the literature. Finally, a proposal for a codifiable 50-year moisture conversion factor (ηcm ) of 0.6 is made for the durability design of pultruded GFRP profiles under permanent exposure to moisture, which is consistent with the partial factor method of the Eurocodes.